Prevention of recognition memory loss and moderation of mitochondrial dynamic tendency toward fusion by flavone derivatives in Aβ-injected rats: a comparison between two flavonoids with different polarity. (3rd April 2019) - Arsalandeh, Farshad; Khodagholi, Fariba; Ahmadian, Shahin; Foolad, Forough; Mohammadi Kamsorkh, Hamed; Moridi Farimani, Mahdi; Shaerzadeh, Fatemeh
Abstract : Growing evidence sheds light on the use of flavonoids as the promising alternatives for the treatment of chronic conditions, including cancer and neurodegenerative disorders. Accordingly, in the present study, we aimed at evaluating the effects of oral intake of two structurally different flavonoids 5-hydroxy-6, 7, 4ʹ-trimethoxyflavone (flavone 1) and 5, 7, 4ʹ-trihydroxyflavone (flavone 2) on recognition memory, hippocampal protein level of immediate early gene cFos and mitochondrial dynamic markers in Amyloid β (Aβ)-injected rats. Recognition aspect of memory and level of proteins were measured using novel object recognition test and Western blot, respectively. Our data indicated that even though flavone 1 was more effective than flavone 2 to prevent memory impairment, feeding with both flavones alleviated memory in Aβ-injected rats. Furthermore, in flavones-administered rats, mitochondrial dynamic balancing returned to the control level by the decline in Dynamin-related protein-1 protein level, a known marker for mitochondrial fission, and elevation in protein level of mitochondrial fusion factors Mitofusins 1 and 2. In parallel with behavior results, flavone 1 was more effectual on mitochondrial dynamic moderating. The more neuroprotective effects of flavone 1 could be attributed to its methylated structure leading to crossing of the blood-brain barrier with ease and metabolic stability and bioactivity.